Unwinding the winding trajectory: The divergence between national accounts and state planning, Argentina 1937-1948 - Lanata Briones, Cecilia T. (2017)
Using primary sources from different official agencies, this paper reconstructs the initial trajectory of Argentine national accounting and sheds light on its divergent path with regards to the state planning carried out by the Peronist administration. Based on the notions of the sociology of quantification framework, it argues that the divergence was grounded on biases, technical arguments and political support that suggest different conceptions about the Argentine economy and society. This article claims that from the mid-1930s and throughout 1940 two groups of experts were formed within the Argentine state that had responsibilities in the design and implementation of economic programmes and policies. Each group had its own vision of the national economy, based on their specific use of statistics.